Use of vegetable fibers as reinforcements in cement-matrix composite materials: A review. (18th July 2022) - Laverde, Valeria; Marin, Angie; Benjumea, José M.; Rincón Ortiz, Mauricio
Graphical abstract: Highlights: Fiber and matrix treatments tend to improve the mechanical behavior of cementitious matrix composites. The use of treatments in cementitious composites increases the fiber–matrix interaction, improving the mechanical behavior of the composites. Short vegetable fibers used as internal reinforcement improve the flexural and tensile strength and the toughness of cement-based composites. Long vegetable fibers used as external reinforcement increase the strength and ductility of cementitious matrix composites under compression. Vegetable fibers are mostly used in non-structural applications such as roof tiles, tiles, and masonry elements. Abstract: The need for sustainable building materials has progressively increased the interest in the use of vegetable fibers as reinforcements in cementitious matrix composites. These fibers are renewable, inexpensive, and offer other advantages, such as lightness, stiffness, biodegradability, and high impact resistance. This review presents research conducted in this field over the last 20 years. For this purpose, the most commonly used fibers and the treatments used to improve the mechanical properties of composites were identified. Moreover, the effect of fiber length on the mechanical properties of the reinforced composites was discussed. Some applications of vegetable-fiber-reinforced composites in structural and nonstructural elements have been highlighted. Based on the results, the treatment used the most was highlighted, which was matrix modifications that reduce the cementitious paste alkalinity by improving the fiber interactions within the composite. Furthermore, short fibers significantly increased the flexural and tensile strengths, and toughness of fiber-reinforced cementitious composites (FRCC), whereas long fibers, used as external reinforcement, increased the compressive strength of textile-reinforced cementitious composites (TRCC) by limiting lateral concrete expansion and abrupt failure. Despite the enhanced mechanical properties of fiber-reinforced composites, information related to fiber durability in cementitious matrices is limited thus far, which has restricted their application in primary structural elements that have high force demands.